2019
DOI: 10.1002/jbm4.10202
|View full text |Cite
|
Sign up to set email alerts
|

How To Build a Bone: PHOSPHO1, Biomineralization, and Beyond

Abstract: Since its characterization two decades ago, the phosphatase PHOSPHO1 has been the subject of an increasing focus of research. This work has elucidated PHOSPHO1's central role in the biomineralization of bone and other hard tissues, but has also implicated the enzyme in other biological processes in health and disease. During mineralization PHOSPHO1 liberates inorganic phosphate (P i ) to be incorporated into the mineral phase through hydrolysis of its substrates phosphocholine (PCho) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 156 publications
(310 reference statements)
0
51
0
Order By: Relevance
“…Gene ontology analysis revealed that biological process of the OMRGs was enriched in the genes enriched at bone mineralization, like down-regulated S1PR1, and up-regulated TWIST1 and PHOSPHO1. Intriguingly, these genes have been shown to target bone formation and bone matrix mineralization (Isenmann et al, 2009;Dillon et al, 2019;Lewis et al, 2019;Xiao et al, 2019). It is likely that there are multiple genes involved in infection-induced changes in bone remodeling, but the relative importance of these distinct genes in bone remodeling during infection remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Gene ontology analysis revealed that biological process of the OMRGs was enriched in the genes enriched at bone mineralization, like down-regulated S1PR1, and up-regulated TWIST1 and PHOSPHO1. Intriguingly, these genes have been shown to target bone formation and bone matrix mineralization (Isenmann et al, 2009;Dillon et al, 2019;Lewis et al, 2019;Xiao et al, 2019). It is likely that there are multiple genes involved in infection-induced changes in bone remodeling, but the relative importance of these distinct genes in bone remodeling during infection remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities of the phenotype described here to that of the Phospho1 -/mouse are clear. As discussed above, ablation of PHOSPHO1 in mice induces hypomineralization in young animals, resulting in rickets/osteomalacia and biomechanical deficiency (9)(10)(11) . Here we report that 4-week Enpp6 -/tibiae exhibit hypomineralized trabecular bone compared with controls, along with a significant increase in SMI indicating a change in trabecular geometry.…”
Section: Accepted Articlementioning
confidence: 92%
“…The biochemical mechanisms through which P i is generated within MVs are currently unclear. Orphan phosphatase 1 (PHOSPHO1; Phospho1) was identified as a novel bone phosphatase critical for mineralization (7)(8)(9) . The PHOSPHO1 knock-out mouse (Phospho1 -/-) displays a hypomineralized skeleton at birth, biomechanical incompetency, scoliosis, and spontaneous greenstick fractures (10,11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHOSPHO1 initiates the hydrolysis of intravesicular metabolites including phosphoethanolamine and phosphocholine to obtain P i . Thus, it has been suggested that PHOSPHO1 functions synergistically with TNAP to accumulate P i into the calcified matrix vesicles [ 57 ]. Moreover supplementation of a PHOSPHO1 inhibitor alone and in combination with a TNAP inhibitor, prevented in vitro VSMC calcification [ 58 ].…”
Section: Purinergic Receptor Independent Pathwaymentioning
confidence: 99%